A Buddhist Ritual of Big Dipper veneration (based on the Tibetan manuscript from Tuvan archives) - Mirzaeva, Saglara V.; Samdan, Ayana A. (The New Research of Tuva, 2021)
The article introduces the text of a Tibetan manuscript “Sme bdun skar ma’i lug gi tshe thar zhes bya ba bzhugs so” (Tshe-thar (freeing life) of the ewe devoted to Big Dipper) preserved in the Tuva Institute of Humanitarian and Applied Socio-Economic Research under the Government of the Republic of Tyva. It contains valuable data on the Buddhist tshe-thar ritual devoted to the Ursa Major constellation. This manuscript probably refers to Mongolian popular Buddhism, since similar texts in Tibetan have been found only in the National Library of Mongolia. The analysis of Tibetan tshe-thar ritual and Mongolian seter carried out in the publication leads us to propose that these rituals in the tradition of Mongolian Buddhism are identical. Ethnographic data on the seter ritual devoted to the Big Dipper show the existence of special texts read by Buddhist lamas during ritual. The manuscript from the Institute’s Tuvan collection could also refer to this group of texts. The text is poetic, containing an appeal to the constellation deities named as Seven Tathagatas, offering to them a white ewe adorned in a special way, and final requests for various benefits, liberation from obstacles, diseases and harmful influences.